2014
DOI: 10.1111/jocs.12465
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Systemic Inflammatory Response After Congenital Cardiac Surgery

Abstract: SIRS after congenital heart surgery is associated with increased mortality. Independent risk factors for SIRS in the patient population of the study were cardiopulmonary bypass time, body weight below 10 kg and preoperative diagnosis of right to left shunt congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 17 publications
5
41
2
4
Order By: Relevance
“…A retrospective study in children applied the same criteria after cardiac surgery and found a lower incidence for SIRS of 8.9% . In contrast to our study, SIRS incidence was determined within a 24‐hour period after cardiac surgery in a cohort of children with an overall higher body weight comparable to our population . However, even during a 24‐hour period, we experienced a higher cumulative SIRS‐incidence of 22.4%.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…A retrospective study in children applied the same criteria after cardiac surgery and found a lower incidence for SIRS of 8.9% . In contrast to our study, SIRS incidence was determined within a 24‐hour period after cardiac surgery in a cohort of children with an overall higher body weight comparable to our population . However, even during a 24‐hour period, we experienced a higher cumulative SIRS‐incidence of 22.4%.…”
Section: Discussioncontrasting
confidence: 81%
“…Left panel presents the amount of fulfilled SIRS criteria at time of first diagnosis. SIRS was defined as presence of at least two out of four criteria (abnormal heart rate, respiratory rate, temperature and leukocyte count) . At least either abnormal temperature or leukocyte count was considered as one obligate criterion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we claim that there shouldn't be any difference also in between CBP periods and between ACC periods in order to have a reliable comparison in terms of systemic inflamatory response; because many studies revealed that systemic inflammatory response is increased by longer periods of CPB and ACC. [3][4][5] In this point, we suggest that the study would be more valuable if the authors share these data with us. …”
mentioning
confidence: 92%
“…1) As the authors stated, strong systemic inflammatory response takes place due to mediators caused by contact of blood and extracorporeal surface during CBP, myocardial ischemia reperfusion secondary to aortic cross-clamping (ACC), endotoxemia and operative trauma. [2][3][4] It is obviously seen that CBP is the most important factor among these. Related to that, when the study of Geyik et al is considered, there is a general standardization of perioperative data between two groups that are distinguished up to operation period.…”
mentioning
confidence: 99%